Relevance of cutaneous manifestations and antineutrophil cytoplasmic antibody status in eosinophilic granulomatosis with polyangiitis - Meiko Sone; Chie Miyabe; Ryujin Miyata; Yuko Takenaka; Naoko Ishiguro (Frontiers Media S.A., 2022)
Abstract Eosinophilic granulomatosis with polyangiitis (EGPA) belongs to the family of antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitis syndromes. Although increasing evidence indicates the correlation of clinical and histological features with the presence or absence of ANCAs in EGPA, the variations in cutaneous features according to their ANCA status have not been fully described. Here, we retrospectively reviewed the clinical and histological findings of 9 cases of EGPA, who presented with cutaneous lesions. Our data indicate that ANCA‐positive patients often present with blisters, systemic inflammatory symptoms, and are prone to receive a higher dose of oral prednisolone and additional immunosuppressive therapies.